1989
DOI: 10.1246/bcsj.62.1528
|View full text |Cite
|
Sign up to set email alerts
|

Optical Resolution of 2′-Methoxy-1,1′-binaphthyl-2-carboxylic Acid, and Application to Chiral Derivatizing Agent for HPLC Separation of Enantiomeric Alcohols and Amines

Abstract: Racemic 2′-methoxy-1,1′-binaphthyl-2-carboxylic acid was separated on a multi-gram scale into its antipodes via silica-gel column chromatography followed by alkaline hydrolysis of the diastereomeric esters prepared from (R)-1-phenylethanol or (−)-menthol. The molecular structure of (−)-menthyl (aS)-2′-methoxy-1,1′-binaphthyl-2-carboxylate was determined by single-crystal X-ray analysis. The (aS)-acid was converted to crystalline acid chloride, which was conveniently utilized as efficient chiral derivatizing ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

1989
1989
2013
2013

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…A mixture of racemic fluorenol 1a (1.00 g, 3.87 mmol), acid chloride (S)-7 16 (1.62 g, 4.67 mmol) and dry pyridine 1-ARYLFLUORENOLS (13 ml) was stirred at room temperature for 20 hr. The mixture was poured into 1 M HCl and extracted with chloroform.…”
Section: Optical Resolution Of Fluorenol 1amentioning
confidence: 99%
“…A mixture of racemic fluorenol 1a (1.00 g, 3.87 mmol), acid chloride (S)-7 16 (1.62 g, 4.67 mmol) and dry pyridine 1-ARYLFLUORENOLS (13 ml) was stirred at room temperature for 20 hr. The mixture was poured into 1 M HCl and extracted with chloroform.…”
Section: Optical Resolution Of Fluorenol 1amentioning
confidence: 99%
“…A mixture of racemic fluorenol 1a (1.00 g, 3.87 mmol), acid chloride (S)-7 16 (1.62 g, 4.67 mmol) and dry pyridine To a cooled solution of the diastereomerically pure ester (+)-8 (205 mg, 0.360 mmol) in THF (3.0 ml) was added LiAlH 4 (27 mg, 0.711 mmol) portionwise at 0°C and the mixture was stirred for 1 hr and then allowed to warm to room temperature. After being stirred at this temperature for a further 3 hr, the mixture was cooled to 0°C and quenched by successive additions of ethanol (1.0 ml), water (1.0 ml) and 1 M HCl (5.0 ml).…”
Section: Optical Resolution Of Fluorenol 1amentioning
confidence: 99%
“…Recently, we and other research groups have shown that 2Ј-methoxy-1,1Ј-binaphthyl-2-carboxylic acid is very useful as a chiral derivatizing agent for the discrimination of enantiomeric alcohols and amines by HPLC or 1 H NMR. 16,[22][23][24] Then we adopted the binaphthylcarboxylic acid as the resolving agent of 1-phenylfluorenol (1a) (Scheme 2). Treatment of racemic fluorenol 1a with 1.2 mol equiv.…”
Section: Optical Resolution Of 1-phenylfluorenol (1a)mentioning
confidence: 99%
“…Many diastereomerizing reagents for RPLC have been developed: e.g., o-phthaladehyde-N-acetyl-Lcystein, [1] (þ)-1-(9-fluorenyl)ethyl chloroformate, [2] (a2)-2 0 -methoxy-1,1 0binaphthyl-2-carboxylate, [3] (S)-(2)(2,3-naphthalene dicarboximidyl)-propionyl fluoride, [4 -6] and chiral monohalo-s-triazines, [7] 4-nitro-7-(3-aminopyrrolidin-1-yl)-2,1,3-benzoxadiazole, [8,9] (1R,2R)-N-[(2-iso-thiocyanato)cyclohexyl]-6methoxy-4-quinolinylamide), [10] and O-(4-nitro-benzyl)-tyrosine methyl ester [11] for racemic amines and/or amino acids. When this method is combined with reversed-phase liquid chromatography (RPLC), it yields very convenient and quick analysis of enantiomer mixtures, although not suitable for fractionating.…”
Section: Introductionmentioning
confidence: 99%